PEMANFAATAN PERSONAL BRANDING KARYAWAN DALAM STRATEGI PEMASARAN DIGITAL BERBASIS KONTEN PADA LAMAN WEB RESMI GOTO - Aditya Bayu Kusuma; Muhammad Fachmi; Dede Yusuf Maulana; Hening Lintang Kinanthi; Mardiman Mardiman (Media Mahardhika, 2026)
This study examines the utilization of employee personal branding within GoTo Group's content based digital marketing strategy on its official website, addressing post merger cultural integration challenges between Gojek and Tokopedia. Employing a qualitative descriptive approach with a single case study design, the research combines content analysis of gotocompany.com (Januari-December 2024), semi structured interviews with three key informants, and a systematic literature review of Scopus indexed journals. Findings reveal a significant gap, GoTo's website remains dominated by corporate narratives without space for employee generated content, despite strong foundations through Employee Resource Groups (±1,200 members). Persona segmentation identified four employee groups (Tech Talent, Sustainability Champions, Merchant Success, Driver Partners) with varying engagement potential. The study proposes the T-I-R-O-C-A implementation framework (Testimonial Internal Resource Organic Amplification Community Analytics), adaptively designed for post merger organizational complexity. ROI projection indicates first year savings up to IDR 13.8 billion through an 81% increase in career page conversion rate and 24% reduction in cost per hire. The findings enrich Indonesia's employer branding literature by positioning employee advocacy as an integrated digital marketing strategy that builds consumer trust through authenticity.